KELOMPOK PENJUAL MAKANAN SECARA ONLINE DI PERUMAHAN GRIYA PANIKI INDAH (GPI) KECAMATAN MAPANGET KOTA MANADO PROPINSI SULAWESI UTARA - Karuntu, Merlyn Mourah; Mandey, Silvya Lefina (The Studies of Social Sciences, 2020)
Griya Paniki Indah (GPI) housing is one of the largest housing estates in North Sulawesi. With more than 7,000 houses built, this housing has become one of the relatively large residential locations. This condition provides an opportunity for the emergence of online food selling businesses in this housing in an effort to meet the needs of the people in the housing. This PKM elevates the community of online food seller groups which are micro, small and medium enterprises (MSMEs) which increase from time to time but often experience dissatisfaction from consumers due to product quality that is not in accordance with what is described in online media, lead time for food delivery is usually more from 1 hour and the inconsistency of the quality of the product produced. The online Food Seller group is an economically productive target audience. This service seeks to address the problem of customer dissatisfaction with online food vendors by making training to provide knowledge and understanding of quality management concepts, especially those related to performance, features, reliability, conformance, durability, serviceability, aesthetic, and perception. AsÂ  wellÂ  as strategies for overall quality improvement through TQM elements, namely customer focus, obsession with quality, long-term commitment, teamwork, continuous system improvement, education and training, unity of purpose, and employee involvement and empowerment.